2020
DOI: 10.1038/s41477-019-0582-x
|View full text |Cite
|
Sign up to set email alerts
|

Introducing selective agrochemical manipulation of gibberellin metabolism into a cereal crop

Abstract: Use of growth retardants enables post-planting optimization of vegetative growth, which is particularly important with the ongoing climate change. Mepiquat chloride is an economical and safe retardant widely applied in cotton, but is not uniformly effective. Here identification of its molecular target as the ent-copalyl diphosphate synthase that initiates gibberellin biosynthesis enabled introduction of selective agrochemical inhibition, leaving intact more specialized metabolism important for resistance to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The unlimited growth of plant height and branch length is certainly a major limiting factor for planting density in cotton fields (Su et al ., 1993). Currently, the quaternary ammonium‐containing compound mepiquat chloride (1,1‐dimethyl‐piperidinium chloride (DPC), which inhibits plant height and branch length, has been widely used to control plant architecture in agriculture practice (Zhang et al ., 2020). However, this management program has raised two nontrivial challenges: rising labor costs and potential harm to farmland eco‐environment by accumulation of residues (Ji et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The unlimited growth of plant height and branch length is certainly a major limiting factor for planting density in cotton fields (Su et al ., 1993). Currently, the quaternary ammonium‐containing compound mepiquat chloride (1,1‐dimethyl‐piperidinium chloride (DPC), which inhibits plant height and branch length, has been widely used to control plant architecture in agriculture practice (Zhang et al ., 2020). However, this management program has raised two nontrivial challenges: rising labor costs and potential harm to farmland eco‐environment by accumulation of residues (Ji et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although MC facilitated cotton fruit development, the underlying physiological mechanism remains unclear; however, He et al (1990) reported that MC could increase the release of ethylene in the later stage of boll development, thereby promoting boll opening. We hypothesize that MC may enhance cotton fruit development by reducing the biosynthesis of gibberellins (Zhang et al, 2020) and altering phytohormone crosstalk, but this is subject to confirmation by future research.…”
Section: Crop Sciencementioning
confidence: 90%
“…Mepiquat chloride (1,1-dimethylpiperidium chloride; DPC) is a synthetic plant hormone that is widely used as a growth retardant in cotton [ 15 – 18 ]. DPC inhibits gibberellin synthesis in plants and can control cotton vegetative growth [ 19 , 20 ], reduce boll shedding, and promote boll development and root growth in cotton [ 10 , 21 , 22 ]. DPC has also been shown to improve cell membrane stability and stress tolerance in plants [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%